Analisis Kritis terhadap Spirit Dekonstruksi dalam Kajian Hermeneutika Kristen Kontemporer - Ferry Simanjuntak; Yosep Belay (Jurnal Ledalero, 2021)
This paper aims to analyze the impact of Derrida's theory of deconstruction in relation to the application of contemporary Christian hermeneutics as well as an attempt at hermeneutical repositioning. The methodological approach used in this paper is descriptive qualitative with instruments of literature study, comparison and textual analysis. Concretely, critical analysis is carried out in stages of deconstruction theory, various phenomena of contemporary Christian hermeneutics, then presents the idea of Christian hermeneutics as a comparative model and discourse criticism. Meanwhile, the body of the writing is divided into three parts according to the analysis pattern. First, it specifically examines Derrida's theory of deconstruction. Second, it is an analysis of several forms of hermeneutic phenomena and discourse of Christian theology which are currently developing. Third, reviewing the Christian hermeneutic discourse from the evangelical perspective in an effort to reposition, criticize, and test discourse on the contemporary worldview. Through this research, distortions were found in hermeneutic studies and contemporary Christian discourse with several forms of deconstruction approaches. The three explicit patterns used are the hermeneutic application of binary negation to conservative theological discourse, the explicit emphasis on the textual eisegesis model and the post-structuralism approach to interpretation..Key words: Dekonstruksi, hermeneutika, oposisi biner, semantic, interpretasi biblis